Efficacy and safety of dihydroartemisinin-piperaquine in Indonesian children infected with uncomplicated Plasmodium falciparum and Plasmodium vivax - Emiliana Tjitra; Delima Delima; Armedy Ronny Hasugian; Hadjar Siswantoro; Rossa Avriana; Ondri Dwi Sampurno (Paediatrica Indonesiana, 2011)
Background Dihydroartemisinin-piperaquine (DPQ) has been used since 2006 in Papua, Indonesia and is planned as an alternative artemisinin-based combination therapy for wider use in Indonesia. Confirmation of the drugâ€™s efficacy and safety in children outside Papua is needed.Objective To measure the day-42 clinical and parasitological efficacy of DPQ in children with uncomplicated falciparum and vivax malaria.Methods This cross-sectional and observational study was held in Kalimantan and Sulawesi in 2010. Seventy and sixty children under 15 years of age with uncomplicated falciparum and vivax malaria were selected according to the 2003 WHO protocol for monitoring therapeutic efficacy of antimalarial treatments and was confirmed by microscopy and PCR. All subjects were treated with DPQ based on a dosage regimen of dihydroartemisinin 2-4 mg/kg BW/dose and piperaquine 16-32 mg/kg BW/dose, in single daily doses for 3 days and closely observed for 42 days. Data was analyzed using intention-to-treat (ITT) and per protocol (PP) populations.Results The mean fever and asexual parasite clearance times were 1.0 day and 1.6 days, respectively, in children with uncomplicated falciparum malaria, and 1.1 days and 1.2 days, respectively, in children with uncomplicatedvivax malaria. Clinical symptoms reduced over 50% by day 7. Hemoglobin recoveries showed improvement on days 14, 28 and 42, at 70.6%, 83.8%and 89.1%, respectively, in the falciparum malaria group, and 60.3%, 65,5% and 83.6%, respectively, in thevivax malaria group. Adequate clinical and parasitological response to DPQ on day 42 in the ITT and PP populations were reported as 98.6% (95% CI 92.3 to 99.7%) and 100% (95% CI 94.7 to 100%), respectively, in the falciparum group, and 91.7% (95% CI 81.9 to 96.4%) and 96.5% (95% CI 88.1 to 99.0%), respectively, the vivax group. Mild adverse events commonly noted were cough, abdominal pain, diarrhea, anorexia, and vomiting.Conclusion DPQ was effective against falciparum and vivax malaria with adequate clinical and parasitological response of â‰¥ 95%, rapid fever and asexual parasite clearance, good hematological recovery and mild adverse events.